(untitled) (Journal of Enam Medical College, 2012)
Myasthenia gravis is the most frequent autoimmune neuromuscular transmission disorder with incidence of 2-20 patients per million. Its pathophysiology is autoimmune, with acetylcholine receptor auto antibodies damaging the post-synaptic fold at the muscle membrane. The diagnostic confirmation of myasthenia gravis is often challenging. Ice-oneyes test can be used to diagnose this disease for its simplicity, safety and cost-effectiveness. Here we report a case of myasthenia gravis in Enam Medical College Hospital, Savar, Dhaka where ice-on-eyes test was done with improvement of ptosis of the patient. Aim of this case report is to make aware our physicians to apply this simple bed side test instead of common traditional edrophonium (tensilon test) test for confirmation of the diagnosis of ocular myasthenia gravis. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12845 J Enam Med Col 2012; 2(2): 92-93